A Framework for Anchor Methods and an Iterative Forward Approach for DIF Detection. (March 2015) - Kopf, Julia; Zeileis, Achim; Strobl, Carolin
In differential item functioning (DIF) analysis, a common metric is necessary to compare item parameters between groups of test-takers. In the Rasch model, the same restriction is placed on the item parameters in each group to define a common metric. However, the question how the items in the restriction—termed anchor items —are selected appropriately is still a major challenge. This article proposes a conceptual framework for categorizing anchor methods: The anchor class to describe characteristics of the anchor methods and the anchor selection strategy to guide how the anchor items are determined. Furthermore, the new iterative forward anchor class is proposed. Several anchor classes are implemented with different anchor selection strategies and are compared in an extensive simulation study. The results show that the new anchor class combined with the single-anchor selection strategy is superior in situations where no prior knowledge about the direction of DIF is available.